2018
DOI: 10.1080/09638237.2018.1487541
|View full text |Cite
|
Sign up to set email alerts
|

Debt, common mental disorders and mental health service use

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 24 publications
6
22
0
2
Order By: Relevance
“…Likewise, our findings are in line with those of other recent studies that found an association of over-indebtedness and common mental disorders including anxiety which also reflect common indications for antidepressant prescriptions [15,11,17]. Previous studies have examined the association of diverse measures of over-indebtedness, such as self-reported problems repaying debts [12,11,17] or mortgage arrears [11,13,16] and mental health outcomes. Longitudinal analyses based on the British Household Panel Survey (BHPS) documented that over-indebtedness was associated with worse mental health outcomes including anxiety and the GHQ Caseness Score [11].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Likewise, our findings are in line with those of other recent studies that found an association of over-indebtedness and common mental disorders including anxiety which also reflect common indications for antidepressant prescriptions [15,11,17]. Previous studies have examined the association of diverse measures of over-indebtedness, such as self-reported problems repaying debts [12,11,17] or mortgage arrears [11,13,16] and mental health outcomes. Longitudinal analyses based on the British Household Panel Survey (BHPS) documented that over-indebtedness was associated with worse mental health outcomes including anxiety and the GHQ Caseness Score [11].…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, the over-indebted were twice as likely to have a depressive disorder (aOR 2.36, 95% CI 1.59-3.50) and generalised anxiety disorder (aOR 2.51, 95% CI 1.85-3.41) [15]. Likewise, evidence from the South East London Community Health (SELCoH) study showed a significant increase in the odds of CMD among over-indebted respondents over time [17]. Moreover, the latter study found an association between continuous over-indebtedness and talking therapy use in the past year even after adjustment for sociodemographic and socioeconomic variables and prior mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health services manage patient populations with complex social and psychiatric needs. Patients with mental health problems are more likely to have experienced financial difficulties, debt, housing issues and unemployment, which may complicate care planning (Evans, 2018;Gunasinghe et al, 2018;Richardson, Jansen, & Fitch, 2018). Mental capacity can fluctuate due to psychiatric symptoms and psychological distress and patients may refuse treatment .…”
Section: Patient Safety Research In Mental Healthmentioning
confidence: 99%
“…Their Head of Research, Katie Evans starts off this issue with a helpful overview of some of the links between financial challenges and mental health problems (Evans, 2018). The links between debt, demographic characteristics and common mental health problems is then investigated in important research by Gunasinghe et al (2018). Two papers using survey data throw light on how individuals with mental health problems get into a spiral of debt.…”
mentioning
confidence: 99%